Association of Celiac Serology Normalization With the Risk of Hypothyroidism: A Cohort Study. (15th September 2022) - Golan, Maya Aharoni; Feldman, Becca; Ollech, Jacob E.; Hoshen, Moshe; Shamir, Raanan; Belfer, Rachel-Gingold; Levi, Zohar
Abstract : INTRODUCTION: We evaluated whether persistent-positive celiac serology is associated with the risk of hypothyroidism. METHODS: We extracted a cohort of subjects aged 1–80 years with a positive IgA anti–tissue transglutaminase between January 1, 2008, and December 31, 2012, and a repeat anti–tissue transglutaminase test within 6–36 months from a large population-based electronic medical record database. Based on serology tests, we categorized the pediatric (age <21 years) and adult cohorts into normalized or persistent-positive serology groups. All subjects were followed up for incident diagnosis of hypothyroidism from the last serology date up to December 31, 2017. Hazard ratio (HR) along 95% confidence intervals (CIs) were prepared to evaluate the association of celiac serology group with a diagnosis of hypothyroidism, crude, and adjusted for age, sex, and diagnosis of type 1 diabetes mellitus. RESULTS: Among the pediatric cohort (n = 2, 687), during a median follow-up of 64 months (interquartile range 48–80), 2.3% (16/681) of the persistent-positive serology group and 1.0% (20/2, 006) of the normalized serology group developed hypothyroidism (HR 2.07 [95% CI 1.07–4.44], adjHR 1.77 [95% CI 0.91–3.46]). The rate among the pediatric cohort with an established diagnosis of celiac disease was 3.4% (10/486) vs 1.0% (5/481), HR 2.83 (0.96–8.32). In the adult cohort (n = 1, 286), 4.5% (20/442) of the persistent-positive group and 3.9% (33/811) of the normalized serology group developed hypothyroidism (HR 1.13 [95% CI 0.65–1.97]). DISCUSSION: In this retrospective, age-stratified analysis, we report that persistent-positive serology may be associated with the risk of hypothyroidism among the pediatric population. Prospective cohorts are needed to validate our findings.